2020
DOI: 10.1111/jpn.13475
|View full text |Cite
|
Sign up to set email alerts
|

Fibre supplementation to pre‐weaning piglet diets did not improve the resilience towards a post‐weaning enterotoxigenic E. coli challenge

Abstract: Dietary fibre (DF) is implicated in gastrointestinal health of weaned piglets, either through its physiochemical properties, through modulation of gut microbiota and (or) improved gut integrity. We aimed to study the effect of DF enriched supplemental diets fed to suckling piglets (‘creep feed’) on health and performance after weaning when challenged with an enterotoxigenic E. coli (ETEC). Seventy‐two piglets originating from 28 litters had been fed four creep diets, that is a low‐fibre control (CON); a diet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…We argue that, at least, the products are unlikely to be detrimental to cellular integrity. Of note, on the contrary, some authors reported detrimental effects of fibers such as cellulose and arabinoxylan [ 130 ], indicating that the outcomes are probably fiber-specific.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that, at least, the products are unlikely to be detrimental to cellular integrity. Of note, on the contrary, some authors reported detrimental effects of fibers such as cellulose and arabinoxylan [ 130 ], indicating that the outcomes are probably fiber-specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to Berrocoso et al [ 335 ], the effect was especially seen in poor sanitary conditions compared with optimal sanitary conditions. When providing piglets additional fibre by adding 2% long-chain arabinoxylans from wheat (lc-AXOS) or 5% purified cellulose or both to a control standard diet, van Hees et al [ 337 ] observed a significant negative effect of lc-AXOS on diarrhoea in the first week post-weaning. Furthermore, intestinal permeability increased when supplying lc-AXOS prior to ETEC (days 7 to 9 post-weaning), whereas after ETEC challenge, cellulose increased permeability.…”
Section: Strategies To Prevent/reduce Post-weaning Diarrhoeamentioning
confidence: 99%
“…Supporting these results, Halas et al [ 130 ] conducted an ETEC F4 challenge study with weaners and measured a reduction in PWD incidence and improved faecal consistency when pigs were fed a diet with 8% added inulin as compared with a inulin-free control. As described above, the study by van Hees et al [ 337 ] showed a negative effect of providing piglets with additional fibre by adding 2% long-chain arabinoxylans from wheat (lc-AXOS) to creep feed on diarrhoea the first week post-weaning and on intestinal permeability.…”
Section: Strategies To Prevent/reduce Post-weaning Diarrhoeamentioning
confidence: 99%
“…As suggested by this and other studies ( Table 3 ), creep feed can also serve a functional role, in which the nutrient composition of the creep feed may be able to modulate gut health. Additional research is nevertheless needed in order to understand the impact of such strategies on post-weaning growth and gut health [ 115 ].…”
Section: Preparing Piglets For Weaningmentioning
confidence: 99%